Analisis SWOT Dalam Pengembangan Strategi Pemasaran Pada Produk Fashion Toko Zelora Lampung - Mediana Rahmatika; Muharia; Tasya Salsabila; Vicky F Sanjaya (Jurnal Akuntansi Dan Manajemen, 2024)
Toko Zelora in Bandar Lampung has emerged as one of the key players in seizing the growing market opportunities in the era of globalization and increasingly intense competition. The purpose of this SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is to identify various internal and external components that influence the marketing performance of Toko Zelora. Internal strengths include high product quality and excellent service, while weaknesses such as dependency on specific suppliers and higher prices, as well as the dangers posed by increasingly fierce competition and the rapid pace of sales, are also identified. This analysis is conducted using an in-depth library research method. It is expected that this analysis will assist the management of Toko Zelora in developing more innovative and flexible marketing strategies. These strategies can enhance the store’s competitiveness in a market that is not only becoming more competitive but also help the fashion business reach more customers, expand its market share, and strengthen its position within the industry. It is hoped that this analysis will provide appropriate recommendations by thoroughly understanding the market dynamics of Bandar Lampung.